Aflibercept for long-term treatment of diabetic macular edema and proliferative diabetic retinopathy: a meta-analysis - Xie, Xiao; Lian, Chao; Zhang, Zhiping; Feng, Meng; Wang, Wenqi; Yuan, Xiaomeng; Shi, Yanmei; Liu, Tingting (Frontiers in Endocrinology, 2023)
Purpose: This meta-analysis compared the long-term (12 months or 24 months) efficacy and safety of intravitreal aflibercept injection (IAI) for diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR). Methods: We selected 16 randomized controlled trials (RCTs) performed after 2015 that had a minimum of 12 months and up to 24 months of treatment and conducted a meta-analysis with Review Manager version 5.3. Visual acuity (VA), central subfield thickness (CST) and adverse events were the outcomes selected for evaluation from the eligible studies. Results: Based on 16 RCTs, we evaluated a total of 7125 patients. For PDR and severe DME with poor baseline vision, after a minimum of 12 months and up to 24 months of treatment, the aflibercept treatment group obtained better VA improvement than the focal/grid laser photocoagulation treatment group (MD=13.30; 95%CI: 13.01~13.58; P<0.001) or other treatments (ranibizumab, focal/grid laser photocoagulation, PRP, et al) group. In addition, the aflibercept treatment group got higher CST reduction than the focal/grid laser photocoagulation treatment group (MD=-33.76; 95%CI: -45.53 ~ -21.99; P<0.001) or other treatments (ranibizumab, focal/grid laser photocoagulation, et al) group (MD=-33.76; 95%CI: -45.53 ~ -21.99; P<0.001). There was no significant difference in the overall incidence of ocular and non-ocular adverse events in each treatment group. Conclusions: This meta-analysis showed that the advantages of IAI are obvious in the management of DME and PDR with poor baseline vision for long-term observation (a minimum of 12 months and up to 24 months) with both VA improvement and CST reduction. Applied IAI separately trended to be more effective than panretinal photocoagulation separately in VA improvement for PDR. More parameters should be required to assess functional and anatomic outcomes.